Impacto da responsabilidade social empresarial no custo de capital próprio das empresas brasileiras: um estudo empírico do período de 2005 a 2009 - Canela, Renata (2010)
As the existing literature on the impact of corporate social investment in the company's financial performance, this study aims to analyze the effect of corporate social responsibility in the cost of capital of companies. The preliminary cost of equity of companies in the Index of the Stock Exchange of Sao Paulo - Bovespa Index, representative of the market and companies participating in the ISE portfolio, representative of corporate social responsibility, for the period 2005 to 2009. As a result, it was noted that in most years studied, there was no significant drop in the cost of equity of companies that are part of the ISE, pointing to the fact that the investment in corporate social responsibility does not affect financial indicators such as cost equity analysis.